PENGARUH PROPORSI TEPUNG PISANG KEPOK (Musa paradisiaca forma typica) DAN OATMEAL (Avena sativa l) TERHADAP HASIL JADI MASKER UNTUK PERAWATAN KULIT WAJAH - Dyah Aura, Rizky Enggar (Universitas Negeri Surabaya, 2023)
Kepok banana flour has abundant benefits such as the content of sources of vitamins C, A, E and flavonoid compounds contained in bananas which have benefits as hypoallergenic, antioxidants and can slow down premature aging. Oatmeal also contains high vitamin E, which is very beneficial for the skin such as refreshing and tightening facial skin. This study aims to determine 1) the effect of the proportions of kepok banana flour and oatmeal on the resulting masks for facial skin care assessed from organoleptic properties which include aroma, color and texture 2) which proportion of masks the panelists liked the most. This type of research is experimental research. The independent variable in this study was the proportion of kepok banana flour and oatmeal, namely X1 (2 grams : 8 grams), X2 (4 grams : 6 grams), X3 (5 grams : 5 grams), X4 (6 grams : 4 grams), X5 ( 8 gram : 2 gram).The dependent variable in this study was the result of the physical properties of banana flour and oatmeal masks which included aroma, color, texture and preference of the panelists. Using the observation method of 30 panelists. The data analysis technique used was single anova test and duncan advanced test. The results showed that 1) the proportion of kepok banana flour and oatmeal (8 grams : 2 grams) was the best facial mask product with the criteria of having a very banana scent, cream/beige color, fairly smooth texture. 2) From the results of the analysis of the level of preference, it was concluded that the best facial masks were found in the proportion of kepok banana flour and oatmeal 8 grams: 2 grams which had an effect on organoleptic properties including aroma, color and texture.Keywords: facial mask, banana flour, oatmeal